1999
DOI: 10.1021/jo9821675
|View full text |Cite
|
Sign up to set email alerts
|

New Lewis-Acidic Molybdenum(II) and Tungsten(II) Catalysts for Intramolecular Carbonyl Ene and Prins Reactions. Reversal of the Stereoselectivity of Cyclization of Citronellal

Abstract: New Mo(II) complexes BnEt(3)N(+)[Mo(CO)(4)ClBr(2)](-) (A) and Mo(CO)(5)(OTf)(2) (B) and their W(II) congeners D and E have been developed as catalysts for the title reactions. Unlike other Lewis acids, the latter catalysts exhibit cis-stereoselectivity in the cyclization of citronellal (1 --> 3 with A and 1 --> 5 with B). Isotopic labeling allowed formulation of the reaction mechanism, according to which these complexes act as bulky Lewis acids, eta(1)-coordinated to the carbonyl oxygen. The stereochemistry ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 82 publications
1
38
0
Order By: Relevance
“…For example, the selective hydrogenation of citral was widely investigated on different metalsupported catalysts for producing either nerol/geraniol or citronellal and citronelol [4,5]. The citronellal cyclization to isopulegol has been carried out by using liquid [6,7] and solid [8][9][10] acid catalysts, while the direct synthesis of menthols from citronellal was recently investigated on ruthenium-based catalysts [11]. In this note we report the development of bifunctional metal-acid catalysts that promote selectively the direct conversion of citral to menthols.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the selective hydrogenation of citral was widely investigated on different metalsupported catalysts for producing either nerol/geraniol or citronellal and citronelol [4,5]. The citronellal cyclization to isopulegol has been carried out by using liquid [6,7] and solid [8][9][10] acid catalysts, while the direct synthesis of menthols from citronellal was recently investigated on ruthenium-based catalysts [11]. In this note we report the development of bifunctional metal-acid catalysts that promote selectively the direct conversion of citral to menthols.…”
Section: Introductionmentioning
confidence: 99%
“…Good selectivities favoring isopulegol can be achieved with zinc salts (ZnBr 2 and ZnI 2 ), 4 although in stoichiometric amounts, and catalytic scandium triflate, 6 whereas neoisopulegol is slightly favored using SbCl 5 4 or molybdenum(II) and tungsten(II) catalysts. 7 We wish to report that citronellal undergoes cyclization in the presence of catalytic amounts of NbCl 5 , TaCl 5 and InCl 3 . 8 NbCl 5 has been successfully used in our group as Lewis acid in a variety of reactions 9 and has gained increasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…We have also demonstrated that the Mo(II) and Mo(IV) complexes A-C act as very mild Lewis-acidic catalysts 11,12 , which is in sharp contrast to Mo(0)-and Pd(0)-complexes, known to react via η 3 -coordinated intermediates 13,14 . In view of the ready availability of the Mo(II) (refs 11e,11h,15 ) and Mo(IV) (refs 12,16 ) catalysts and their compatibility with various nucleophiles, it was of interest to extend this methodology to the carbohydrate realm with a view of developing a simple, non-expensive route to various C-glycosides, based on the Mo-catalyzed allylic substitution in the glycal molecule.…”
mentioning
confidence: 82%